LA PSICOLOGÍA DEL COLOR EN LOGOTIPOS DE LOS PERIÓDICOS IMPRESOS EN ECUADOR: IMPLICACIONES EN IDENTIDAD Y PERCEPCIÓN EN LA AUDIENCIA - ALVARADO POSLIGUA JULEXSY KATHERINE (2024)
The use of color psychology in logos printed in Ecuador is fundamental to developing the visual identity of the medium, considering it as a primary strategy that goes beyond just aesthetics, it also involves the transmission of a message and the image that is desired to be projected. for users, since through these components the audience can be impacted immediately to speed up and facilitate its recognition. In this study, the psychology of color was directriz investigated, the different colorimetries used and the most prominent colors in newspapers printed in the context of Ecuador, as well as chromatic selection and its impact on the identity and perception of its audience. Finally, it should be noted that the psychology of color in the logos of printed newspapers in Ecuador can strengthen the image of the medium and its visibility in society. Furthermore, if the chromatic selection is used appropriately in a logo, the result will be identification with the newspaper, easy recognition of its image, and its colors will always remain in the minds of users, this being a competitive and innate advantage.